Caracterização da integração entre as áreas funcionais na perspectiva de tríades: estudos de caso em organizações industriais - Seno, João Paulo (2014)
The differentiation between functional areas is necessary for organizations to be able to meet the challenges posed by the environment. This same differentiation, however, requires the functional integration for organization can operate to achieve their goals and use their resources efficient. This paper uses the perspective of triads, an approach of Social Psychology that studies groups of subjects for the analysis of phenomena associated with the relationships between functional areas of an organization. This approach has been used recently in the study of the relationship between organizations in supply chains. Multiple case studies was conducted in three industrial companies in the region of Uberlandia (MG) and six categories of phenomena that help to understand the relationship between functional areas were identified: Urgency, Capacity vs. Demand, Motivation, Challenge and Respect. Existing theories that adopt the perspective of triads, the Theory of Balance of Heider, Theory of Structural Holes, by Simmel and Theory of Coalitions by Caplow were also used for data analysis. Seven propositions were made regarding the phenomena associated with functional integration from the perspective of triads that can contribute to future studies in this research field.